A Case Report of Dialysis Catheter Placement in an Anomalous Pulmonary Vein - Cierra King; Karling Gravenstein (Case Reports in Vascular Medicine)
Conclusions: Central line placement is a commonly performed procedure in hospitals. There are steps that have been developed to limit complications for this procedure, including ultrasound guidance, visualization of venous blood, and confirmatory imaging prior to use. This is a case in which arterial-appearing blood, paO2, and chest x-ray were concerning for incorrect placement, but additional imaging revealed accurate access with anomalous anatomy. Overall, the case of central line placement in anomalous pulmonary venous connections is rare but needs consideration when the clinical scenario is appropriate.